1999
DOI: 10.1111/j.1939-1676.1999.tb02205.x
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Partial Pericardiectomy in 13 Dogs

Abstract: Thirteen dogs with cardiac tamponade resulting from pericardial effusion were prospectively evaluated to determine feasibility and outcome of thoracoscopic partial pericardiectomy. A lateral thoracoscopic approach allowed adequate exposure to remove a 4- to 5-cm-diameter section of pericardium in all dogs. Complete resolution of cardiac tamponade occurred in all dogs for which there was follow-up (11 dogs). Ten of 13 dogs (76.9%) had neoplastic pericardial effusion. One of these dogs remains alive at 220 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 11 publications
(12 reference statements)
1
72
1
4
Order By: Relevance
“…Eliminating conventional abdominal incisions is considered to have a number of potential advantages including faster recovery and thus a shorter hospital stay, decreased postoperative pain, improved postoperative pulmonary function and improved cosmetic outcome. Previous studies have also confirmed the safety and benefits of VATS in thoracic cavity surgery (3,4).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Eliminating conventional abdominal incisions is considered to have a number of potential advantages including faster recovery and thus a shorter hospital stay, decreased postoperative pain, improved postoperative pulmonary function and improved cosmetic outcome. Previous studies have also confirmed the safety and benefits of VATS in thoracic cavity surgery (3,4).…”
Section: Introductionmentioning
confidence: 73%
“…A number of comparative studies on VATS procedures in animals have evaluated stress parameters and postoperative outcomes (7,8); there have also been studies into the outcomes of VATS lobectomy (4,9). Compared with VATS, hemithorax pneumonectomy is more difficult to perform and there is a higher risk of intra-and post-operative complications occurring (10); thus, the degree of stress and the postoperative hemodynamics in VATS compared with traditional open pneumonectomy remains to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…disturbance, shock, oliguria and prolonged anesthesia time (Jackson et al, 1999) thoracoscopy is preferred to manage pericardial disease and effusions (Jackson et al, 1999;Palsgaard et al, 2007;Bicer et al, 2015). Considering this and previous postoperative clinical results, comparative investigation of the partial pericardiectomy through thoracotomy and thoracoscopic pericardial window techniques was planned in an experimental animal model.…”
Section: Histopathological Findingsmentioning
confidence: 99%
“…P ericardiectomy techniques are performed in both humans and animals to treat neoplastic or non-neoplastic pericardial diseases (Kerstetter et al, 1997;Busch et al, 2015), especially pericardial effusions (Kerstetter et al, 1997;Jackson et al, 1999). The presenting malignant, infectious or idiopathic etiologies may indicate the need for pericardiectomy in small animals (Dupre et al, 2001;Case, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation